IMPLEMENTASI METODE PENDEKATAN SENTRA DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF PADA ANAK KELOMPOK B DI TK AURA SATU SUMBERJAYA KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - nur hidayati (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
This research aims to describe central learning at kindergarten institutions in Pati Regency. Using qualitative research, in the form of data regarding the implementation of the central learning model, the steps for implementing central learning, and children’s progress obtained through the learning process using the central learning model. The object of this research consists of three institutions in different sub-districts, namely: Aisyiah 2 Pati Kindergarten, Bintang Kecil Kindergarten and An-Nismah Kindergarten. The subjects of this research include: teachers, school principals and students from the three institutions. Data collection techniques used passive participant observation, semi-structured interviews, and documentation. The results of this research show that kindergarten institutions in Pati Regency implement central learning using four play steps, including: structuring the play environment, steps before playing, steps during play and steps after playing. However, each institution has differences in the implementation of learning centers, distribution of activity time, and distribution of teachers.